Behavior representation and simulation for Military Operations on Urbanized Terrain (MOUT) - Shen, Zhuoqian (2008)
This thesis presents our research on behavior representation and simulation for MOUT. First of all, a layered AI framework for the artificial players (bots) has been proposed. The framework is designed to be flexible, extensible, integrable and independent of simulation platforms. The functionality of each module and the interfaces between each other have been specified. Secondly, for fast prototyping, the AI framework is implemented on the Unreal Tournament (UT) game engine which provides high-fidelity whilst affordable 3D virtual environments.